2022
DOI: 10.2147/jaa.s357086
|View full text |Cite
|
Sign up to set email alerts
|

Annual and Post-Exacerbation Follow-Up of Asthma Patients in Clinical Practice – A Large Population-Based Study in Sweden

Abstract: Background Symptom control has not improved in Swedish asthma patients during the last two decades. Guidelines recommend annual reviews for asthma patients treated with maintenance inhaled corticosteroids (ICS). We aimed to describe how visit patterns in an ICS-treated asthma population in Sweden were related to applicable asthma guidelines. Methods Swedish electronic health data for incident asthma patients, ≥18 years, with at least one ICS collection (index date) betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This may be since these patients who purchased SABA without prescriptions did not regularly follow up with their physicians and therefore did not receive accurate and up-to-date information about their condition [ 35 , 45 , 75 ]. Sandelowsky et al (2022) reported that asthma patients who regularly visit primary and secondary care have higher adherence to inhaled corticosteroids [ 76 ]. All healthcare providers play a major role in managing asthma patients who purchase SABA medication over-the-counter.…”
Section: Discussionmentioning
confidence: 99%
“…This may be since these patients who purchased SABA without prescriptions did not regularly follow up with their physicians and therefore did not receive accurate and up-to-date information about their condition [ 35 , 45 , 75 ]. Sandelowsky et al (2022) reported that asthma patients who regularly visit primary and secondary care have higher adherence to inhaled corticosteroids [ 76 ]. All healthcare providers play a major role in managing asthma patients who purchase SABA medication over-the-counter.…”
Section: Discussionmentioning
confidence: 99%